The Molecular Interactions That Stabilize RNA Tertiary Structure: RNA Motifs, Patterns, and Networks - Butcher, Samuel E; Pyle, Anna Marie (Accounts of chemical research, 2011)
RNA molecules adopt specific three-dimensional structures critical to their function. Many essential metabolic processes, including protein synthesis and RNA splicing, are carried out by RNA molecules with elaborate tertiary structures (e.g. 3QIQ, right). Indeed, the ribosome and self-splicing introns are complex RNA machines. But even the coding regions in messenger RNAs and viral RNAs are flanked by highly structured untranslated regions, which provide regulatory information necessary for gene expression. RNA tertiary structure is defined as the three-dimensional arrangement of RNA building blocks, which include helical duplexes, triple-stranded structures, and other components that are held together through connections collectively termed RNA tertiary interactions. The structural diversity of these interactions is now a subject of intense investigation, involving the techniques of NMR, X-ray crystallography, chemical genetics, and phylogenetic analysis. At the same time, many investigators are using biophysical techniques to elucidate the driving forces for tertiary structure formation and the mechanisms for its stabilization. RNA tertiary folding is promoted by maximization of base stacking, much like the hydrophobic effect that drives protein folding. RNA folding also requires electrostatic stabilization, both through charge screening and site binding of metals, and it is enhanced by desolvation of the phosphate backbone. In this Account, we provide an overview of the features that specify and stabilize RNA tertiary structure. A major determinant for overall tertiary RNA architecture is local conformation in secondary-structure junctions, which are regions from which two or more duplexes project. At junctions and other structures, such as pseudoknots and kissing loops, adjacent helices stack on one another, and these coaxial stacks play a major role in dictating the overall architectural form of an RNA molecule. In addition to RNA junction topology, a second determinant for RNA tertiary structure is the formation of sequence-specific interactions. Networks of triple helices, tetraloop–receptor interactions, and other sequence-specific contacts establish the framework for the overall tertiary fold. The third determinant of tertiary structure is the formation of stabilizing stacking and backbone interactions, and many are not sequence specific. For example, ribose zippers allow 2'-hydroxyl groups on different RNA strands to form networks of interdigitated hydrogen bonds, serving to seal strands together and thereby stabilize adjacent substructures. These motifs often require monovalent and divalent cations, which can interact diffusely or through chelation to specific RNA functional groups. As we learn more about the components of RNA tertiary structure, we will be able to predict the structures of RNA molecules from their sequences, thereby obtaining key information about biological function. Understanding and predicting RNA structure is particularly important given the recent discovery that although most of our genome is transcribed into RNA molecules, few of them have a known function. The prevalence of RNA viruses and pathogens with RNA genomes makes RNA drug discovery an active area of research. Finally, knowledge of RNA structure will facilitate the engineering of supramolecular RNA structures, which can be used as nanomechanical components for new materials. But all of this promise depends on a better understanding of the RNA parts list, and how the pieces fit together.